Signed Directed Graph based modeling and its validation from process knowledge and process data - Yang, Fan; Shah, Sirish L.; Xiao, Deyun (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with the fusion of information from process data and process connectivity and its subsequent use in fault diagnosis and process hazard assessment. The Signed Directed Graph (SDG), as a graphical model for capturing process topology and connectivity to show the causal relationships between process variables by material and information paths, has been widely used in root cause and hazard propagation analysis. An SDG is usually built based on process knowledge as described by piping and instrumentation diagrams.
Keywords: signed directed graph; transfer entropy; process topology; fault diagnosis; process hazard assessment